Chronic Hepatitis B Relapse Rates after Cessation of Tenofovir Alafenamide and Entecavir Therapy - Chih-Wen Huang; Chen-Ta Yang; Pei-Yuan Su; Yang-Yuan Chen; Siou-Ping Huang; Hsu-Heng Yen (Biomedicines, 2023)
Chronic hepatitis B (CHB) relapse occurs after the cessation of nucleos(t)ide analogues (NUC) therapy due to the waning of viral suppression. Few studies have investigated the viral relapse rate and clinical relapse rate after tenofovir alafenamide (TAF) therapy. We compared the CHB relapse rate between TAF and entecavir therapy. We enrolled patients with chronic hepatitis B who underwent TAF or entecavir therapy. NUC therapy was terminated after HBeAg loss for 1 year in HBeAg-positive patients and after undetectable serum HBV DNA on three separate tests each >6 months apart in HBeAg-negative patients. After cessation of NUC therapy, we followed alanine aminotransferase (ALT) levels at 12, 24, and 48 weeks. Serum HBV DNA levels were checked if patients showed a two-fold elevation from the upper limit of normal ALT levels (41 IU/mL). Clinical relapse (CR) was defined as a two-fold elevation in ALT levels and HBV DNA levels > 2000 IU/mL. We then investigated the CR rate of HBV after cessation of TAF and entecavir therapy at 12, 24, and 48 weeks. Of the 117 patients enrolled, 78 were in the entecavir group and 39 were in the TAF group. At 12 weeks after cessation of NUC therapy, no patients had HBV CR in the entecavir group. However, three patients (CR cumulative rate 7.9%) had CR in the TAF group. At 24 weeks, the CR cumulative rate in the entecavir and TAF groups were 1.3% and 13.2%, respectively (p < 0.05). At 48 weeks, the CR cumulative rates were 9.2% and 24.2%, respectively (p = 0.055). Patients in the TAF group had a higher cumulative rate of CR than those in the entecavir group (log-rank p = 0.023). Furthermore, patients in the TAF group had earlier CR times than those in the entecavir group, especially in the first 24 weeks after cessation of therapies (p < 0.05). The cessation of TAF therapy had significantly earlier and higher CR rates than that of entecavir therapy. Close monitoring of liver function and HBV DNA levels may be necessary, especially within 24 weeks after cessation of TAF therapy.